2013
DOI: 10.1002/hipo.22120
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume predicts fluid intelligence in musically trained people

Abstract: Recently, age-related hippocampal (HP) volume loss could be associated with a decrease in general fluid intelligence (gF). In the present study we investigated whether and how extensive musical training modulates human HP volume and gF performance. Previously, some studies demonstrated positive effects of musical training on higher cognitive functions such as learning and memory, associated with neural adaptations beyond the auditory domain. In order to detect possible associations between musical training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 85 publications
5
27
0
2
Order By: Relevance
“…In line with the key role of rhythm in mediating the emotional valence and arousal induced by music, musical pulse, or rhythm has also been shown to engage amygdala and hippocampus (Alluri et al, 2012; Toiviainen et al, 2014), the latter playing a role also in auditory working memory (Burunat et al, 2014). Musical training has also been linked to increased hippocampal and amygdala volume (Oechslin et al, 2013; Dohn et al, 2015; Vaquero et al, 2016), providing converging support for our finding of decreased volume of these structures in non-recovered amusia.…”
Section: Discussionsupporting
confidence: 63%
“…In line with the key role of rhythm in mediating the emotional valence and arousal induced by music, musical pulse, or rhythm has also been shown to engage amygdala and hippocampus (Alluri et al, 2012; Toiviainen et al, 2014), the latter playing a role also in auditory working memory (Burunat et al, 2014). Musical training has also been linked to increased hippocampal and amygdala volume (Oechslin et al, 2013; Dohn et al, 2015; Vaquero et al, 2016), providing converging support for our finding of decreased volume of these structures in non-recovered amusia.…”
Section: Discussionsupporting
confidence: 63%
“…The hippocampus is involved in various higher cognitive functions (24) such as fluid intelligence (25) and different aspects of memory including working memory (26)(27)(28), but also declarative/episodic memory, constructive memory, and spatial navigation (29,30). Beauchamp et al found that hippocampal volumes in preterm born infants assessed at term equivalent age correlated with working memory deficits at the age of 2 y (13).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, a recent study by Oechslin et al (2013) found that fluid intelligence is predicted by the volume of the hippocampus in musicians, which suggests that musical training could be used as a strategy to reduce age-related decline of fluid intelligence. In another study by Hanna-Pladdy and Mackay (2011), significant differences between elderly musicians and non-musicians (60–83 years) were found in non-verbal memory, verbal fluency, and executive functions.…”
Section: Plasticity Over the Life-spanmentioning
confidence: 99%